INTEGRATIVE MODEL OF ISLAMIC RELIGIOUS EDUCATION AND GUIDANCE AND COUNSELING IN STRENGTHENING STUDENTS' CHARACTER BASED ON EMOTIONAL INTELLIGENCE IN THE DIGITAL ERA - Markos Toni; Ahmad Jamin; Bukhari Ahmad (Institut Agama Islam Negeri (IAIN) Curup, 2026)
This study aims to develop an integrative model of Islamic Religious Education (IRE) and Guidance and counseling in strengthening students’ character based on emotional intelligence in the digital era. The research employed a mixed methods approach with a sequential explanatory design. The qualitative phase used a case study approach to explore the implementation of IRE and Guidance and counseling integration in schools, while the quantitative phase measured students’ emotional intelligence and character through structured questionnaires. The findings revealed that IRE plays an important role in internalizing moral and religious values, whereas Guidance and counseling contributes to improving emotional regulation and social interaction. Quantitative results showed that 28% of students had high emotional intelligence, 54% moderate, and 18% low. However, the integration between IRE and Guidance and counseling remains partial and unsystematic. This study proposes an integrative model positioning IRE as the source of values, emotional intelligence as the mediating variable, and Guidance and counseling as the psychological intervention approach. The model contributes to the development of holistic character education through the integration of cognitive, affective, and social dimensions.